WORK-FAMILY CONFLICT DAN IMPLIKASINYA TERHADAP KEPUASAN KERJA DAN STRES KERJA: STUDI PADA LEMBAGA PENYIARAN PUBLIK TVRI SULAWESI TENGGARA - Trisno Trisno; Zulkifli Zulkifli; Al Asy Ari Adnan Hakim (Mega Aktiva, 2023)
ABSTRACTThis study aims to examine the effect of employees’ job satisfaction through job stress at the Public Broadcasting Institution TVRI Southeast Sulawesi. This research employs a quantitative approach with an exploratory research design. The study was conducted at the Public Broadcasting Institution TVRI Southeast Sulawesi with a research sample of 83 employees selected through a census method. The analytical method used was multiple linear regression with Partial Least Squares (PLS), which is a Structural Equation Modeling (SEM) technique. The findings reveal that work-family conflict and job stress have a significant positive effect on employees’ job satisfaction at the Public Broadcasting Institution TVRI Southeast Sulawesi. It was also found that work-family conflict has a significant positive effect on employees’ job stress. Furthermore, the mediation analysis shows that work-family conflict significantly influences job satisfaction through job stress at the Public Broadcasting Institution TVRI Southeast Sulawesi.